Congenital Hypothyroidism: Increased Incidence in Yazd Province, Iran - M. Noori-Shadkam; M.H. Mosadegh; M. Mirzaei; MR. Movahedi Nia; M. Jafarizadeh (Shahid Sadoughi University of Medical Sciences, 2012)
Introduction: Congenital hypothyroidism (CH) is one of the most common preventable causes of mental retardation. Its worldwide incidence is estimated to be one in 2500-5500 births. Assessment of thyroid gland in neonates is critical. The aims of this study were to demonstrate the incidence of CH in neonates born in Yazd province, Iran in 1389 (2010) and compare the results with other reported studies and investigate biochemical characteristics of affected infants. Materials & Methods: This is an analytical descriptive cross-sectional study. The study was conducted on all infants (13022 births) born in 1389 (March 2010-March 2011). Thyroid stimulating hormone (TSH) was measured using ELISA technique. Results: Forty five infants suffered from congenital hypothyroidism with an overall incidence of one in 289 live births. Twenty five of the diagnosed infants were males (incidence 1:261) and twenty were females (incidence 1:325). The incidence of CH in boys was more than girls (P-value = 0.295). The highest incidence of CH was observed in spring followed by summer and the lowest incidence was in autumn followed by winter (P-value=0.000. Conclusion: The CH incidence was 10.3 to 13.8 times more than other countries. The highest CH incidence was in spring followed by summer and the lowest incidence was in autumn followed by winter. It is important that a larger size of cases need to be screened and more information on the aetiology of the affected infants to be obtained